Automated solid-phase synthesis of oligosaccharides containing sialic acids - Lai, Chian-Hui; Hahm, Heung Sik; Liang, Chien-Fu; Seeberger, Peter H. (Beilstein Journal of Organic Chemistry, 2015)
A sialic acid glycosyl phosphate building block was designed and synthesized. This building block was used to prepare α-sialylated oligosaccharides by automated solid-phase synthesis selectively.
Keywords: α-sialylation; automated synthesis; glycosylation; sialic acid; solid-phase synthesis

Essentials of glycobiology - Varki, A.; Cummings, R. D.; Esko, J. D.; Freeze, H. H.; Stanley, P.; Bertozzi, C. R.; Hart, G. W.; Etzler, M. E. (Cold Spring Harbor Laboratory Press, 2009)

(untitled) - Adak, A. K.; Yu, C.-C.; Liang, C.-F.; Lin, C.-C. (Curr. Opin. Chem. Biol., 2013)

(untitled) - Varki, A. (Nature, 2007)

(untitled) - Plante, O. J.; Palmacci, E. R.; Seeberger, P. H. (Science, 2001)

(untitled) - Kröck, L.; Esposito, D.; Castagner, B.; Wang, C.-C.; Bindschädler, P.; Seeberger, P. H. (Chem. Sci., 2012)

(untitled) - Hurevich, M.; Seeberger, P. H. (Chem. Commun., 2014)

(untitled) - Eller, S.; Collot, M.; Yin, J.; Hahm, H. S.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kandasamy, J.; Schuhmacher, F.; Hahm, H. S.; Klein, J. C.; Seeberger, P. H. (Chem. Commun., 2014)

(untitled) - Walvoort, M. T. C.; Volbeda, A. G.; Reintjens, N. R. M.; van den Elst, H.; Plante, O. J.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Org. Lett., 2012)

(untitled) - Calin, O.; Eller, S.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2013)

(untitled) - Esposito, D.; Hurevich, M.; Castagner, B.; Wang, C.-C.; Seeberger, P. H. (Beilstein J. Org. Chem., 2012)

(untitled) - Lin, C.-C.; Lin, N.-P.; Sahabuddin, L. S.; Reddy, V. R.; Huang, L.-D.; Hwang, K. C.; Lin, C.-C. (J. Org. Chem., 2010)

(untitled) - Tanaka, H.; Nishiura, Y.; Takahashi, T. (J. Am. Chem. Soc., 2006)

(untitled) - Chu, K.-C.; Ren, C.-T.; Lu, C.-P.; Hsu, C.-H.; Sun, T.-H.; Han, J.-L.; Pal, B.; Chao, T.-A.; Lin, Y.-F.; Wu, S.-H.; Wong, C.-H.; Wu, C.-Y. (Angew. Chem., Int. Ed., 2011)

(untitled) - Hsu, C.-H.; Chu, K.-C.; Lin, Y.-S.; Han, J.-L.; Peng, Y.-S.; Ren, C.-T.; Wu, C.-Y.; Wong, C.-H. (Chem. – Eur. J., 2010)

(untitled) - Kancharla, P. K.; Navuluri, C.; Crich, D. (Angew. Chem., Int. Ed., 2012)

(untitled) - Kancharla, P. K.; Kato, T.; Crich, D. (J. Am. Chem. Soc., 2014)

(untitled) - Weishaupt, M. W.; Matthies, S.; Seeberger, P. H. (Chem. – Eur. J., 2013)

(untitled) - Seeberger, P. H. (Chem. Soc. Rev., 2008)

(untitled) - Ratner, D. M.; Murphy, E. R.; Jhunjhunwala, M.; Snyder, D. A.; Jensen, K. F.; Seeberger, P. H. (Chem. Commun., 2005)

(untitled) - Hofmann, J.; Hahm, H. S.; Seeberger, P. H.; Pagel, K.

(untitled) - Mandhapati, A. R.; Rajender, S.; Shaw, J.; Crich, D. (Angew. Chem., Int. Ed., 2015)

(untitled) - Kalikanda, J.; Li, Z. (J. Org. Chem., 2011)

(untitled) - Ngoje, G.; Addae, J.; Kaur, H.; Li, Z. (Org. Biomol. Chem., 2011)

(untitled) - Park, J.; Kawatkar, S.; Kim, J.-H.; Boons, G.-J. (Org. Lett., 2007)

(untitled) - Demchenko, A.; Stauch, T.; Boons, G.-J. (Synlett, 1997)

(untitled) - Fair, R. J.; Hahm, H. S.; Seeberger, P. H. (Chem. Commun., 2015)